THE EFFECT OF YOUTUBE ADVERTISING ON CONSUMER PURCHASE DECISION OF HAPPY MEAL PRODUCTS (A STUDY USING EPIC MODEL) - Hartono, Salman Alfarizi Fanda (Jurnal Ilmiah Mahasiswa FEB, 2021)
The Internet is completely different from other traditional media. Marketing Communication is needed by every business organization because Marketing communications are the means by which firms attempt to inform, persuade, and remind consumers directly or indirectly about the products and brands they sell. One of marketing communication major modes are advertising. YouTube as one of the social media where people or brand can experience varying degrees of engagement with videos, ranging from casual viewing to sharing videos to maintain social relationships. YouTube have a feature that is YouTube ads service. YouTube ads service is a feature of advertising that can advertise directly by businesspeople. Knowing the rapid development of advertising in social media, especially YouTube. This study aims to finding out the effect between YouTube Advertising and Epic Model on Purchase Decision. The Sample size of this research used 150 respondents. This research used primary data collected using a survey technique from people who watch about Happy Meals YouTube advertising and buy the product afterwards. The findings of this study show that empathy, persuasion, impact, communication, and advertising have a significant influence on the purchase decision.Keywords: Advertising, EPIC model, Youtube, Purchase Decision